2019
DOI: 10.1080/2162402x.2018.1561120
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of circulating PD-1, PD-L1, pan-BTN3As, BTN3A1 and BTLA in patients with pancreatic adenocarcinoma

Abstract: PDAC is one of the most heterogeneous cancers with low chemotherapeutic sensitivity due to a dense stroma, a weak vasculature and significant biological aggressivity. In cancer, suppressive immune checkpoints are often hyper-activated to ensure an effective evasion of tumor cells from immune surveillance. These immune checkpoints include in part, the B7/butyrophilin-like receptors such as butyrophilin sub-family 3A/CD277 receptors (BTN3A), the B and T lymphocyte attenuator (BTLA) belonging to the B7-like recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
123
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(128 citation statements)
references
References 30 publications
4
123
0
1
Order By: Relevance
“…The BTN3A isoforms is overexpressed in several tumors and involved in the antitumor function of Vγ9Vδ2 cytolytic T-cells. 27 The findings in this study confirm its involvement in the anti-tumor immune response and a potential role as target of novel antitumoral treatments.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The BTN3A isoforms is overexpressed in several tumors and involved in the antitumor function of Vγ9Vδ2 cytolytic T-cells. 27 The findings in this study confirm its involvement in the anti-tumor immune response and a potential role as target of novel antitumoral treatments.…”
Section: Discussionsupporting
confidence: 75%
“…24 Among several immune checkpoints, a family of transmembrane glycoproteins belonging to the immunoglobulin (Ig) superfamily, called butyrophilins (BTNs), has been recently shown to have an interesting immunomodulatory role. [25][26][27] Based on these evidence, we investigated the potential role of sPD-1, sPD-L1, and sBTNs (pan-sBTN3A, sBTN3A1, and sBTN2A1) levels as predictive biomarkers of response to nivolumab treatment in mccRCC patients (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…1a). A previous study on pancreatic adenocarcinoma also indicated a negative correlation between plasma levels of sBTLA and OS 28 . BTLA is expressed www.nature.com/scientificreports www.nature.com/scientificreports/ in immune cells, including T cells 29 , and inhibits T cell activation in the late phase of immune responses 30 .…”
Section: Discussionmentioning
confidence: 68%
“…A previous study indicated that the up-regulation of BTLA gene expression and soluble BTLA (sBTLA) was validated in thymoma-associated myasthenia gravis [11]. A prognostic investigation showed that the levels of immune checkpoints sBTLA could be considered as a biomarker for unresectable pancreatic adenocarcinoma cases with a poor survival [12]. A functional study identified that IFN-γ level in circulating T-lymphocytes could be promoted by inhibiting BTLA/HVEM pathway [13].…”
Section: Introductionmentioning
confidence: 99%